MENGEMBANGKAN AKTIVITAS DAN MOTORIK HALUS MENGGUNAKAN MODEL PROJECT BASED LEARNING, DIRECT INSTRUCTION DAN MEDIA PLAYDOUGH - Fitria, Nava Vathul; Maimunah, Maimunah (TEACHING : Jurnal Inovasi Keguruan dan Ilmu Pendidikan, 2025)
ABSTRACT The problem in this research focuses on the lack of learning activities and children's imitation skills, which are caused by the learning method which is still one-way (teacher-centered) and the lack of activities that can stimulate children's fine motor skills. This research takes a position as an alternative solution to this problem by implementing the Project Based Learning type and Direct Instruction as well as the use of playdough media to improve imitation skills. The research utilizes qualitative steps with the type of Classroom Action Research (CAR) which was carried out during 4 meetings in group B of Aisyiyah Bustanul Athfal 1 Banjarmasin Kindergarten with a total of 11 students. Data collection techniques include observation of teacher activities, children's activities, and assessment of imitation skills, with analytical descriptive data analysis and cross tabulation through the presentation of tables, graphs, and percentage interpretation. Research findings show that teacher activities have increased from "Quite Good" to "Very Good", children's activities have increased from 9% to 90%, and imitation skills have increased from 18% to 90%. This research concludes that the application of the PjBL, Direct Instruction, and playdough media is effective in increasing teacher activity, child activity, and children's fine motor skills in imitation activities. ABSTRAK Permasalahan pada penelitian ini berfokus dengan minimnya aktivitas belajar serta keterampilan meniru bentuk anak, yang disebabkan oleh metode pembelajaran yang masih bersifat satu arah (teacher-centered) serta kurangnya kegiatan yang mampu menstimulus keterampilan motorik halus anak. Penelitian ini mengambil posisi sebagai solusi alternatif terhadap permasalahan tersebut dengan menerapkan tipe Project Based Learning serta Direct Instruction juga penggunaan media playdough untuk meningkatkan keterampilan meniru bentuk. Riset pemanfaatan langkah kualitatif dengan jenis Penelitian Tindakan Kelas (PTK) yang dilakukan selama 4 kali pertemuan di kelompok B TK Aisyiyah Bustanul Athfal 1 Banjarmasin dengan total murid sejumlah 11 anak. Teknik pengumpulan data meliputi observasi aktivitas guru, aktivitas anak, dan penilaian keterampilan meniru bentuk, dengan analisis data deskriptif analitik dan cross tabulasi melalui penyajian tabel, grafik, serta interpretasi persentase. Temuan riset memperlihatkan aktivitas guru bertambah dari “Cukup Baik” ke “Sangat Baik”, kegiatan anak meningkat dari 9% ke 90%, serta keterampilan meniru bentuk bertambah dari 18% ke 90%. Penelitian ini menyimpulkan penerapan model PjBL, Direct Instruction, serta media playdough efektif dalam meningkatkan aktivitas guru, aktivitas anak, juga keterampilan motorik halus anak dalam aktifitas meniru bentuk.